Genetic Variants in Double-Strand Break Repair Pathway Genes to Predict Platinum-Based Chemotherapy Prognosis in Patients With Lung Cancer - Liu, Jun-Yan; Zou, Ting; Yin, Ji-Ye; Wang, Zhan; Liu, Chong; Huang, Han-Xue; Ding, Fei-Xiang; Lei, Meng-Rong; Wang, Ying; Liu, Min; Liu, Zhao-Qian; Tan, Li-Ming; et al. (Frontiers in Pharmacology, 2022)
Objective: The purpose is to investigate the associations of genetic variants in double-strand break (DSB) repair pathway genes with prognosis in lung cancer patients treated with platinum-based chemotherapy. Methods: 399 lung cancer patients were recruited in this research who received platinum-based chemotherapy at least two cycles. A total of 35 single nucleotide polymorphisms (SNPs) in DSB repair, base excision repair (BER), and nucleotide excision repair (NER) repair pathway genes were genotyped, which were applied to evaluate the overall survival (OS) and the progression-free survival (PFS) of patients with platinum-based chemotherapy prognosis by Cox proportional hazard models. Results: We found that the PFS of patients who carried MAD2L2 rs746218 GG genotype was shorter than AG or AA genotypes (recessive model: P=0.039, OR =5.31, 95% CI =1.09-25.93). Patients with TT or GT genotype of TNFRSF1A rs4149570 had a prominently shorter OS time than patients with GG genotype (dominant model: P=0.030，OR=0.57，95% CI =0.34-0.95). We also investigated the statistically prominent differences between age, gender, histology, smoking, stage, metastasis, which influences the OS and PFS of lung cancer patients. The Single Nucleotide Polymorphisms (SNPs) of DNA repair genes were statistically significant with PFS and OS in subgroup analyses. Conclusion: Our research revealed that variants in the MAD2L2 rs746218 and TNFRSF1A rs4149570 were associated with shorter PFS time or OS time in lung cancer patients with platinum-based chemotherapy, which may be potential new biomarkers for predicting the prognosis.